2009
DOI: 10.1111/j.1523-5378.2009.00689.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Helicobacter pylori Infection in Asymptomatic Children: A Prospective Population‐Based Study from the Czech Republic. Application of a Monoclonal‐Based Antigen‐in‐Stool Enzyme Immunoassay

Abstract: This study of a large cohort of children demonstrated that, independent of gender, H. pylori infection in the Czech Republic is among the lowest reported in Europe. Socioeconomically disadvantaged children, unfortunately, are still at risk of harboring this potentially preventable infection in this low-prevalence region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
49
2
10

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 54 publications
10
49
2
10
Order By: Relevance
“…The prevalence observed in this study was higher than reported for most European countries, and even many South American, African and Asian settings [19][20][21][22], where it ranged from less than 10% to 64%. The prevalence of infection was 69% in Vietnam, in adolescents aged between 10 and 14 years evaluated in 2005 [23], 78% Fig.…”
Section: Discussioncontrasting
confidence: 78%
“…The prevalence observed in this study was higher than reported for most European countries, and even many South American, African and Asian settings [19][20][21][22], where it ranged from less than 10% to 64%. The prevalence of infection was 69% in Vietnam, in adolescents aged between 10 and 14 years evaluated in 2005 [23], 78% Fig.…”
Section: Discussioncontrasting
confidence: 78%
“…This finding is in agreement with other studies [3739, 41, 42]. Education may mediate the observed association by influencing personal and household hygiene practices.…”
Section: Discussionsupporting
confidence: 93%
“…W badaniu 1545 bezobjawowych dzieci w wieku 0-15 lat, wykonywanym metodą oznaczania antygenów H. pylori w kale, zakaże-nie stwierdzono u zaledwie 7,1% badanej grupy [19].…”
Section: Omówienieunclassified
“…Zagęszczenie lokali mieszkalnych jest znanym niezależnym czynnikiem ryzyka zakażenia H. pylori, co podkreślają autorzy wielu publikacji poświęconych epidemiologii zakażeń tą bakterią [6,19,22]. Interesującym zjawiskiem jest natomiast wykazany przez nas znacząco wyższy odsetek zakażeń u dzieci mieszkających w dużym, 200-tysięcznym mieście w porównaniu z małym miastem, liczącym ok. 10 tys.…”
unclassified